The relationship between financial development and energy consumption in South Africa - Palesa Milliscent Lefatsa; Kin Sibanda; Rufaro Garidzirai (Economies, 2021)
This paper examines the nexus between financial development and energy consumption in South Africa. To determine the long run and short run relationship between financial development and energy consumption in South Africa, the paper uses an Auto Regressive Distributed Lag bounds test (ARDL) and Granger causality test to establish the type of correlation between 1980 and 2018. ARDL bounds testing method offers concrete long-run estimates and t-statistics as it is flexible whether the adopted variables are I(0) or I(1). The study used per capita (kilogram, kg of oil equivalent) to measure total energy consumption, domestic credit to the private sector (percentage of gross domestic product, GDP) to measure financial development, real GDP growth (to capture economic growth), industrial value added (percentage of GDP) to measure industrialization, and urban population (percentage of total population) to capture urbanization. Results from ARDL showed that the relationship between financial development and energy consumption is positive in nature both in short-run and long-run. Granger causality test results revealed unidirectional causality from financial development to energy consumption. Policymakers need to formulate policy reforms that channels more credit to private sector development in order to bolster more energy use in South Africa. There ought to be proper balance between financial development and energy consumption to avoid electricity crisis.
Keywords: 330; South Africa; economic growth; Granger causality; ARDL; energy consumption; financial development; industrialization; urbanization